Anti-Biofilm Activity of Ethanol Extract of Citrus hystrix Dc. Against Opportunistic Pathogenic Microbes In-Vitro - Budiarti, Lia Yulia; Khatimah, Husnul; Ridhoni, Muhammad Zaki; Hafizhah, Ghina; Fachriyad, Muhammad; Arietama, George (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
Opportunistic pathogenic microbes are often a problem in the treatment of infections because of their ability to form biofilms. The structure of the irreversible components of the glycocalyx or microbial capsule plays a role in protecting it from antimicrobial exposure and disinfection. The effectiveness of antibiofilms needs to be evaluated, including those from natural preparations. Citrus hystrix DC. (C.hystrix) contains antimicrobial compounds and its activity as an antibiofilm needs to be known. This experimental research aims to test the anti-biofilm effect of C.hystrix extract against standard microbial isolates. The dilution method with tube-test was used to analyze the antibiofilm effect of a combination of C. hystrix leaf and peel extracts (6.25%, 12.5%, 25%, 50%, 75%, and 100%) with 70% ethanol control. Antibiofilm observations are qualitatively based on the Minimum Biofilm Inhibitory Concentration (MBIC) and quantitatively based on the Mean Gray Value (MGV) of biofilm intensity. The results of observations in 3 experiments showed that the MBIC of C.hystix extract was 6.25% for gram-positive bacteria and 12.5% for gram-negative bacteria and Candida. The average MGV of C.hystrix extract was 75%, equivalent to 70% ethanol for all test microbes (p.0.05). The highest average MGV was produced by 100% combination extracts for S.epidermidis (138,09±0,36), S.aureus (135,69±2,01), E.coli (134,75±0,89), P.aeruginosa (130,76±0,24), and C.albicans (130,41±0,41). In conclusion, hystrix orange leaf and peel extracts produce anti-biofilm activity against test microbes in-vitro.